GREEN HYDROGEN MODELING IN INDONESIA : POTENTIAL FOR PRODUCTION, CONSUMPTION AND GREEN HOUSE GAS (GHG) EMISSIONS - Yoane Monalisa, Grace
In 2019, national greenhouse gas (GHG) emissions reached 1,845.1 billion tons of CO2e for the 5 main gases (CO2, CH4, N2O, C2F6, CF4), an increase of 15% compared to the previous year. To overcome this problem, the Indonesian government has launched a net zero emission by 2060, and is actively developing the potential for new renewable energy (EBT), one of which is green hydrogen. Green hydrogen was developed to reduce the use of fuels derived from fossil energy. The results of this study are that it is estimated that Indonesia can produce 608 million BOE green hydrogen in 2030, which is equivalent to 123,063 MW. This figure exceeds the target stated in the 2021-2030 PLN RUPTL document, which is 44,320 MW. To produce 1 million BOE green hydrogen, 0.42 MW of power is needed with 24-hour operational hours, and the water that is electrolyzed is sea-coastal water. Every 1 million BOE consumption of green hydrogen can reduce GHG emissions by 0.06 to 0.51 billion tons of CO2e. The largest reduction in GHG emissions is predicted to occur in 2027, namely from 506.69 billion tonnes of CO2e to 485.48 billion tonnes of CO2e. In that year, consumption of green hydrogen rose from 415.76 million BOE to 457.33 million BOE. The resistivity of water and the power used in the electrolysis process are the main factors during the green hydrogen production process. The recommended type of water is coastal seawater with a resistivity of 0.3 ?m or sea wateropen sea with a resistivity of 0.2 ?m. The EBT generator that has the greatest power potential in Indonesia is the Solar Power Plant (PLTS) with a potential of 207.75 GW. The green hydrogen production process can be carried out by utilizing a portion of Indonesia's current surplus power, which is 3.63 GW. Using only a power surplus of 0.1 GW and a rate of additional power of 1.1 GW per year in coastal seawater in the simulation model, it is estimated that Indonesia will achieve net zero emissions by 2030.